Assessment of the total precipitable water from a sun photometer, microwave radiometer and radiosondes at a continental site in southeastern Europe - Fragkos, Konstantinos; Antonescu, Bogdan; Giles, M. David; Ene, Dragos; Boldeanu, Mihai; Efstathiou, A. Georgios; Belegante, Livio; Nicolae, Doina N. (My University, 2019)
In this study, we discuss the differences in the total precipitable water (TPW), retrieved from a Cimel sun photometer operating at a continental site in southeast Europe, between version 3 (V3) and version 2 (V2) of the AErosol RObotic NETwork (AERONET) algorithms. In addition, we evaluate the performance of the two algorithms comparing their product with the TPW obtained from a collocated microwave radiometer and nearby radiosondes during the period 2007-2017. The TPW from all three instruments was highly correlated, showing the same annual cycle, with lower values during winter and higher values during summer. The sun photometer and the microwave radiometer depict the same daily cycle, with some discrepancies during early morning and late afternoon due to the effect of solar zenith angle on the measurements of the photometer. The TPW from V3 of the AERONET algorithm has small differences compared with V2, mostly related to the use of the new laboratory-based temperature coefficients used in V3. The microwave radiometer measurements are in good agreement with those obtained by the radiosonde, especially during night-time when the differences between the two instruments are almost negligible. The comparison of the sun photometer data with high-quality independent measurements from radiosondes and the radiometer shows that the absolute differences between V3 and the other two datasets are slightly higher compared with V2. However, V3 has a lower dependence from the TPW and the internal sensor temperature, indicating a better performance of the retrieving algorithm. The calculated one-sigma uncertainty for V3 as estimated, from the comparison with the radiosondes, is about 10 %, which is in accordance with previous studies for the estimation of uncertainty for V2. This uncertainty is further reduced to about 6 % when AERONET V3 is compared with the collocated microwave radiometer. To our knowledge, this is the first in-depth analysis of the V3 TPW, and although the findings presented here are for a specific site, we believe that they are representative of other mid-latitude continental stations.
Keywords: Southern Europe; AERONET; air temperature; algorithm; assessment method; laboratory method; measurement method; microwave radiometer; photometer; precipitable water; radiosonde; seasonal variation; sensor; zenith angle